2014
DOI: 10.5430/jha.v3n6p205
|View full text |Cite
|
Sign up to set email alerts
|

A modular simulation study to improve patient flow to inpatient units in the emergency department

Abstract: In this study, a modular discrete event simulation (computer modeling) has been presented to support process improvements in a hospital's emergency department (ED) to streamline admitted patient flow to inpatient units. Because the ED in this study has less than 10 beds, unnecessary occupation of beds affects the patient wait time dramatically. Additionally, ED overcrowding diminishes the quality of care, increases costs, and decreases employee and patient satisfaction. The modular simulation model evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…A recent overview in [17] outlines this variety in terms of resulting research questions. Many of the existing papers in this area study reasons for excessive patient waits and discuss strategies to overcome crowded emergency departments [25,30,34,36]. Patient flows and overcrowding of departments appear to be common themes in recent years [12], both of which resonate with the purpose of our work.…”
Section: Pathway Redesign In Emergency Departmentssupporting
confidence: 57%
“…A recent overview in [17] outlines this variety in terms of resulting research questions. Many of the existing papers in this area study reasons for excessive patient waits and discuss strategies to overcome crowded emergency departments [25,30,34,36]. Patient flows and overcrowding of departments appear to be common themes in recent years [12], both of which resonate with the purpose of our work.…”
Section: Pathway Redesign In Emergency Departmentssupporting
confidence: 57%
“…Although physician-to-patient ratio determines the exact impact, increased staffing allows patients to stay for more thorough testing and treatment and more accurate determination of whether and when they should be admitted. Paul and Lin (2012) showed that adding one physician to the ED can significantly reduce overcrowding to positively affect care (Norouzzadeh et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…[18] Workflow improvements have proven to be efficient if they are implemented simultaneously. [19] Gayathri and Klein studied case management as one way to reduce ED visits by FUs and found a reduction of ED use. Other strategies used to affect ED utilisation by FUs were individualised care plans, patient education, primary care partnerships and managed care level interventions.…”
Section: A Challenge To Improve Ed Servicesmentioning
confidence: 99%